Public vs. Private Sector Banks in India: A Theoretical Comparison of Efficiency and Governance (International Journal of Food and Nutritional Sciences, 2023)
This paper examines the theoretical foundations underpinning efficiency and governance differences between public and private sector banks in India. The Indian banking sector presents a unique dualistic structure where government-owned public sector banks (PSBs) operate alongside personally-owned banks, each governed by distinct organizational doctrines and nonsupervisory fabrics. Through relative theoretical analysis predicated in agency proposition, property rights proposition, and institutional proposition, we explore how ownership structures unnaturally impact functional performance, governance mechanisms, threat operation practices, and stakeholder responsibility. Our analysis reveals that private sector banks demonstrate superior functional efficiency through request discipline, professional operation autonomy, and technology- driven optimization, while PSBs maintain strategic advantages in fiscal addition, network penetration, and systemic stability. still, PSBs face patient governance challenges including political hindrance, regulatory decision- timber, and binary authorizations that produce efficiency trade- offs. The findings suggest that neither ownership model proves widely superior; rather, each serves distinct functions within India's different banking ecosystem. This exploration contributes to the ongoing policy debate regarding banking sector reforms, connection strategies, and the optimal balance between marketable efficiency and social banking objects in arising husbandry.